Trusting the Dentist-Expecting a Leap of Faith vs. a Well-Defined Strategy for Anxious Patients - Rod Moore (MDPI AG, 2022)
This article aimed to set into perspective the unique aspects of trust within the dentist-patient relationship by exploring the literature as well as historical aspects of dentistry in the association between trust/distrust and patient anxiety. In order to characterise this uniqueness, the assumptions for trusting in dentistry are compared and contrasted with other professions using a conceptual analysis. The professions of medicine, sociology, psychology, nursing and dentistry were check listed according to the tenets of a concept analytical approach reported by Hupcey et al., in 2001. Recommendations for patient/person-centred care, as opposed to dentist-centred care, that would improve trust are specified according to the literature. These include empowering patients, practicing active listening, empathy and relationship building that might benefit dental patients in relation to the perceived risks of anxiety or induced pain. It was concluded that global distrust of dominating dentists must give way to person-centred professional strategies so that dentists and patients can tackle their dental anxiety-trust challenges, both in the public's image of the dental profession and in clinical relationships. Future directions would be to explore incentives for dentists to change to patient/person-centred care.